Impact of the chemical form of different fluorine sources on the formation of AlF molecules in a C2H2/N2O flame. Issue 4 (2nd February 2016) - Acker, Jörg; Bücker, Stefan; Hoffmann, Volker
Abstract : The positions for the appearance of AlF molecules in a C2 H2 /N2 O flame and the corresponding sensitivity of the AlF molecular absorbance depend on the bonding state of the used fluorine source HF, H2 SiF6, HBF4 and CF3 COOH. Abstract : The formation of diatomic AlF molecules was studied in a C2 H2 /N2 O flame by means of a high-resolution continuum source flame absorption spectrometer using different fluorine containing compounds HF, H2 SiF6, HBF4 and CF3 COOH as fluorine sources. The fragmentation of these fluorine sources, as well the resulting impact on the AlF molecule formation, was derived from flame height distribution studies of the atomic and molecular species Al, AlO, Si, SiO, SiF, B and BF as a function of the fluorine concentration, the molar Al : F ratio and the burner gas composition. As a consequence, the used fluorine sources HF, H2 SiF6, HBF4 and CF3 COOH have been divided into two major groups. The first group of fluorine sources, covering HF, H2 SiF6 and HBF4, decomposes during the drying of the aerosol under the formation of AlF3, which is the dominating species for the transport of aluminium into the flame. Its decomposition into AlF results in a high sensitivity of AlF molecular absorption at low flame observation heights. The second group of fluorine sources is exemplarily given by CF3 COOH. In the upper parts of the flame the cleavage of the very stable C–F bond proceeds incompletely so that the sensitivity of the AlF molecular absorption is considerably lower than that for the other fluorine sources. In consequence, the AlF molecules are formed by the reaction between the fluorine atoms and the aluminium atoms, which are transported into the flame without the aid of fluorine, presumably via oxidic and/or carbidic species. The present investigations show that the sensitivity of the AlF molecular absorption and the pathway of AlF formation depend on the chemical form of the fluorine in the studied samples.